Attitudes and beliefs about medical cannabis among social work students: Cross-national comparison. (May 2021) - Findley, Patricia A.; Edelstein, Offer E.; Pruginin, Itay; Reznik, Alexander; Milano, Nicole; Isralowitz, Richard
Highlights: 230 social work students from the US and 187 from Israel participated in an online survey assessing cannabis attitudes. Most of US and Israeli social work students reported no formal education about Medical Cannabis yet would recommend for clients. Participants who reported any cannabis use, compared to non-users, were more likely to believe MC could benefit physical or mental health. Secular, compared to religious students, believed it has more benefits for physical and/or mental health. Abstract: Objectives: Worldwide, considerable attention is being given to cannabis use for medical conditions. In the current study, we sought to assess attitudes and beliefs about MC among social work students from the US and Israel. Methods: We sought to assess attitudes and beliefs about MC among a sample of 417 social work students (230 from the US and 187 from Israel) who voluntarily participated in an anonymous online survey. Chi-square tests were used to analyze differences between groups. Results: Most of the US and Israeli participants (84.3 % and 96.7 %, respectively) reported no formal education about MC; and, they would recommend MC for their clients. Participants who reported any cannabis use, compared to non-users, were more likely to believe MC could benefit physical or mental health and less inclined to believe use of the substance poses serious physical or mental health risks. Secular, compared to religious students, believed it has more benefits for physical and/or mental health. Conclusions: Our findings evidence a considerable dearth of formal evidence-based education about cannabis for medical conditions in two university-based cohorts, despite beliefs in MC as useful for physical and mental health conditions. Efforts to develop curricula and training programs for social work students are needed since they will be among key professionals addressing client needs from health care and counseling perspectives.